The economic variable that influence of poverty rate in Malaysia / Nurul Atikah Faizul - Faizul, Nurul Atikah (2016)
The most important focuses on this study to find out the significant influence between variables which consist of Unemployment Rate, Inflation Rate, Economic Growth and Income Inequality with the Poverty rate in Malaysian. The researcher found that the entire variable given the significant influence and the multiple regression technique has been used in order to make out the influence. From the equation, it can bring to a close that the three independent variables which are Unemployment Rate, Inflation Rate and Income Inequality are positive significant to Poverty Rate and one independent variable, Economic Growth is negative significant to Poverty Rate. The data gain from the secondary sources. The researcher found that problem from the poverty is important to overcome